2020
DOI: 10.1021/acs.jpcb.0c06081
|View full text |Cite
|
Sign up to set email alerts
|

In-Cell Detection of Conformational Substates of a G Protein-Coupled Receptor Quaternary Structure: Modulation of Substate Probability by Cognate Ligand Binding

Abstract: While the notion that G protein-coupled receptors (GPCRs) associate into homo-and hetero-oligomers has gained more recognition in recent years, a lack of consensus remains among researchers regarding the functional relevance of GPCR oligomerization. A relatively recent technique, Förster resonance energy transfer (FRET) spectrometry, allows for the determination of the oligomeric (or quaternary) structure of proteins in living cells via analysis of efficiency distributions of energy transferred from optically … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 92 publications
(290 reference statements)
2
25
0
Order By: Relevance
“…Such a shape made branched/closed quaternary structures more energetically favorable. Dynamic and compact oligomeric structures have been reported for the Ste2 receptor by FRET ( Paprocki et al., 2020 ). The coupling of mini Gs further enhanced this shift to more compact configurations in which some of the signaling partners made contacts with one another.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a shape made branched/closed quaternary structures more energetically favorable. Dynamic and compact oligomeric structures have been reported for the Ste2 receptor by FRET ( Paprocki et al., 2020 ). The coupling of mini Gs further enhanced this shift to more compact configurations in which some of the signaling partners made contacts with one another.…”
Section: Resultsmentioning
confidence: 99%
“…The adenosine 2a receptor (A2aR) was found to form higher-order oligomers at the plasma membranes ( Glukhova et al., 2017 ; Vidi et al., 2008a ), whereas β 1 adrenergic receptors formed only monomers and dimers ( Calebiro et al., 2013 ). The kinetics of GPCR oligomerization has been reported to be dynamic ( Dijkman et al., 2018 ) and regulated by receptor density ( Calebiro et al., 2013 ) and by ligand ( Möller et al., 2020 ; Paprocki et al., 2020 ). The oligomerization landscape is made more complex by diverse oligomeric structures.…”
Section: Introductionmentioning
confidence: 99%
“…One type of cell sample contained a pair of plasmids,(pYF1988 and pYF2034), each of which contained a gene encoding the sterile2 α-factor receptor fused in frame to a gene encoding one of two variants of the green fluorescent protein (GFP)—i.e., either GFP2 [ 55 ] (PYF1988) or YFP [ 56 ] (PYF2034). Ste2 is the protein of interest in this study, while the GFP2 and YFP tags serve as markers of the Ste2 in separate fluorescence microscopy-based studies of this receptor [ 20 , 53 , 57 ]. The other type of cell sample, referred to as Ste2Δ throughout the manuscript, contained a pair of plasmids comprising the same DNA as the first plasmid pair except those coding DNA for the Ste2–fluorescent protein complex.…”
Section: Methodsmentioning
confidence: 99%
“…However, a high degree of uncertainty still clouds the use of these methods for detection of the agonist based GPCR activation. While some investigators have reported large changes to FRET- and BRET-derived signals upon agonist binding to certain GPCRs [ 17 , 18 , 19 , 20 , 21 , 22 ], others have failed to detect any difference in signal after agonist stimulation of other receptors [ 23 , 24 , 25 , 26 , 27 ]. One challenge that such methods face is that agonist-induced conformational changes to the receptors of interest are not necessarily accompanied by significant changes in the position and/or orientation of the fluorescent tags needed to detect the FRET or BRET signal [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation